Актуальні проблеми функціонування державної служби України в умовах реалізації реформ: соціологічний аспект - Карпунець, Анастасія Станіславівна; Карпунець, Анастасия Станиславовна; Karpunets, Anastasiia S. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Необхідність реформування системи державної служби та державного управління як соціального інституту актуалізує дослідження проблем, спроможних уповільнити або нівелювати процес змін. Зокрема, виокремлено такі з них, як відсутність балансу централізації та децентралізації системи державного управління, відсутність ефективної комунікації між владними структурами й владою та суспільством, дефіцит якісних кадрів, низькі якість адміністративних послуг і рівень морально-етичної свідомості державних службовців та, як наслідок, негативний баланс довіри з боку суспільства. Результатом упровадження реформи має стати створення ефективної, прозорої, відкритої та гнучкої структури публічної адміністрації із застосуванням технологій е-урядування й становлення інституту державної служби як обслуговуючої структури. In the article considered the actual problems faced by the institute of State Service of Ukraine on the aggravation of social, economic and political crisis such as lack of balance of centralization and decentralization of public administration, poor communication, shortage of quality staff, poor quality of administrative services and the low level of moral and ethical consciousness of public servants and as a result negative balance of trust from society. Author emphasizes the need of transformation of the public administration's social role and its functioning as a service structure. There is a need for a new management elite, which requires management skills, ability to work for a result, rapid decisions making, self-management and ready to initiate and manage changes. The civil service and public administration reform problems in the light of the country's citizen’s assessments analyzed. The main task of reform at this stage of Ukraine is determined by establishing sustainable balance of centralization and decentralization and establishment of an effective mechanism of checks and balances as a necessary condition for ensuring democracy, effectiveness of public administration and European integration.
Actual Problems of Civil Service of Ukraine under Implementation of Reforms: Sociological Aspects
Keywords: інститут державної служби України; державне управління; реформування державної служби; баланс централізації та децентралізації; трансформація; institute of civil service of Ukraine; state administration; reform of civil service; balance of centralization and decentralization; transformation